Electron diffraction data processing with DIALS. Issue 6 (6th June 2018) - Clabbers, Max T. B.; Gruene, Tim; Parkhurst, James M.; Abrahams, Jan Pieter; Waterman, David G.
Abstract : Adaptations to the DIALS package are described that make it a suitable choice for processing challenging continuous‐rotation electron diffraction data. The results of using the extended package are presented for a case consisting of seven example data sets. Abstract : Electron diffraction is a relatively novel alternative to X‐ray crystallography for the structure determination of macromolecules from three‐dimensional nanometre‐sized crystals. The continuous‐rotation method of data collection has been adapted for the electron microscope. However, there are important differences in geometry that must be considered for successful data integration. The wavelength of electrons in a TEM is typically around 40 times shorter than that of X‐rays, implying a nearly flat Ewald sphere, and consequently low diffraction angles and a high effective sample‐to‐detector distance. Nevertheless, the DIALS software package can, with specific adaptations, successfully process continuous‐rotation electron diffraction data. Pathologies encountered specifically in electron diffraction make data integration more challenging. Errors can arise from instrumentation, such as beam drift or distorted diffraction patterns from lens imperfections. The diffraction geometry brings additional challenges such as strong correlation between lattice parameters and detector distance. These issues are compounded if calibration is incomplete, leading to uncertainty in experimental geometry, such as the effective detector distance and the rotation rate or direction. Dynamic scattering, absorption, radiation damage and incomplete wedges of data are additional factors that complicate data processing. Here, recent features of DIALS as adapted to electron diffraction processing are shown, including diagnostics for problematic diffraction geometry refinement, refinement of a smoothly varying beam model and corrections for distorted diffraction images. These novel features, combined with the existing tools in DIALS, make data integration and refinement feasible for electron crystallography, even in difficult cases.